Public Basic Schools in Southern Sudan and the Sultanate of Oman (Comparative Study) - Arop, Arop Deng Kuol (Journal of Education and Practice, 2023)
Purpose: This study aims to compare the status of public basic schools in South Sudan and that of the Sultanate of Oman (one of the Gulf countries). Methodology: A search of the relevant literature was incorporated into the work technique. The research was carried out with consideration given to previous theoretical literature, both that which had been published and that which had not. This study focuses on conducting a literature review examining prior research on why South Sudan is left behind. At the same time, other backward countries succeed in narrowing the gap between them and the second-world countries. Findings: The findings revealed three categories of primary schools in South Sudan. Category 1 is primary schools for children whose fathers have looted, corrupted, or stolen public treasure through illegal activities and smuggled government money to Uganda, Kenya, Australia, Europe, the U.S.A or Canada after Comprehensive Peace Agreement (C.P.A) in 2005. These children received a good education in the diaspora. They do not come home until they finish their studies and receive good jobs as stakeholders in government ministries or organizations, and they are primarily paid in hard currency. This category is excluded from our study. Category 2 is primary schools for children who left the country with their parents before or after independence and live in refugee camps in Uganda, Kenya or Egypt. They also receive a good education and enjoy free food in their centres. This category is also excluded from our research. Category 3 is primary schools for children whose parents are displaced inside the country or citizens with nowhere to go. Their children receive poor education in government primary schools and free food from organizations or World Food Program (W.F.P). However, these organizations turned South Sudan to be free nutritional zone. This primary school category is included in our study and is our concern. But in the Sultanate of Oman, the government has an evident vision and willingness to reform and develop the educational sector in the country, and a good potion is given to the development of education in the annual national budget. Unique Contribution to Theory, Policy, and Practice: By conducting the comparative study, it seeks to improve educational circumstances and address flaws in the system. The research will provide insights to the government, donors, and international organizations, prompting support and funding to develop an organized and planned educational system in South Sudan. Ultimately, this study aims to bridge the academic gap and pave the way for positive changes in the country's schooling system.